Pelatihan Pasca Panen dan Pengolahan Jambu Biji Merah untuk Petani di Kecamatan VII Koto Sungai Sariak Padang Pariaman - Wenny Surya Murtius; Purnama Dini Hari (Warta Pengabdian Andalas, 2019)
Community service activities carried out in District VII Koto Sungai Sariak, Padang Pariaman Regency. Partners who act as training participants were red guava’s farmers who already have a garden and have harvested. Priority problems faced by partners were not yet understanding about post-harvest handling and processing of red guava. The training method was participatory, where the activity was carried out by providing training and conducting joint processing practices. The results of the activity showed that the participants were very enthusiastic in participating in the training and included joint practices. So after the training the participants had understood the techniques of post-harvest handling and processing of red guava into several products. Post-harvest handling delivered include picking methods, handling after picking, and primary and secondary packaging used. The processing practice carried out during the training was the manufacture of red guava jam. The expectation of this activity is the implementation of appropriate post-harvest handling and the availability of processed guava products in Kecamatan VII Koto Sungai Sariak, Padang Pariaman Regency.